Micro-PL analysis of high current density resonant tunneling diodes for THz applications - Cito, M.; Cimbri, D.; Childs, D.; Baba, R.; Harrison, B. A.; Watt, A.; Mukai, T.; Wasige, E.; Hogg, R. A. (Applied physics letters, 2021)
Low-temperature micro-photoluminescence (μPL) is used to evaluate wafer structural uniformity of current densities >5mA/μm2 InGaAs/AlAs/InP resonant tunneling diode (RTD) structures on different length scales. Thin, highly strained quantum wells (QWs) are subject to monolayer fluctuations, leading to a large statistical distribution in their electrical properties. This has an important impact on the RTD device performance and manufacturability. The PL spot size is reduced using a common photolithography mask to reach a typical high Jpeak for a given RTD mesa size (1 ∼ 100 μm2). We observe that for lower strain-budget samples, the PL line shape is essentially identical for all excitation/collection areas. For higher strain-budget samples, there is a variation in the PL line shape that is discussed in terms of a variation in long-range disorder brought about by strain relaxation processes. The RTD operating characteristics are discussed in light of these findings, and we conclude that strain model limits overestimate the strain budget that can be incorporated in these devices. We also highlight μPL as a powerful nondestructive characterization method for RTD structures.